ANALISIS PENGEMBANGAN WISATA SELANCAR DI PANTAI PASIR PUTIH SAWARNA, BANTEN - Rosyadi, Kartika Ilma; Cahyadi, Ferry Dwi; Sasongko, Agung Setyo (Social Landscape Journal, 2023)
Sawarna White Sand Beach is one of the beaches in Lebak Regency, which is located in the south of Java Island and directly adjacent to the Indian Ocean. It has surfing potential which is quite famous to foreign countries. It turns out that the existing tourism potential has not been properly supported by the community and local government, the management of tourism which is still lacking makes these tourism objects tend to be left behind and not managed properly. The purpose of this study is to determine the suitability and carrying capacity of the surfing tourism area at the Sawarna White Sand Beach tourist attraction, and to formulate alternative strategies that can be applied in developing surfing tourism at that location. This analysis uses the calculation of the suitability index formula for surfing tourism, the formula for the carrying capacity of the beach tourism area for the surfing category, and SOAR analysis. The results of the analysis that has been carried out show the results of the suitability value of surfing tourism in Surf Zone 1 of 95% which belongs to the S1 category (very suitable), while the suitability value of surfing tourism in Surf Zone 2 is 65% which belongs to the S2 category (suitable), with the carrying capacity of the surfing tourism area as measured along Surf Zone 1 and Surf Zone 2 is 65 people/day. As for the results of the analysis that has been carried out using the SOAR matrix, there are 3 leading alternative strategies that can be carried out in developing surfing tourism at the Sawarna White Sand Beach tourist attraction in the form of forming management and placing human resources in managing more complex and organized tourism objects, carrying out development the availability of supporting facilities for complete and sustainable surfing tourism, and also followed by tourism promotion through the provision of surfing championship events held at the Sawarna White Sand Beach tourist attraction.